Analisis Faktor-Faktor yang Mempengaruhi Kualitas Laporan Keuangan pada BPPKAD Kota Surakarta - Ika Diah Purwati; Indra Lila Kusuma; Maya Widyana Dewi (ITB AAS INDONESIA, 2022)
Abstract This study aims to determine the application of government accounting standards, internal control systems, and human resource competencies have a simultaneous and partial effect on the quality of financial reports. This research was conducted at BPPKAD Surakarta with a total sample of 49. This type of research is quantitative with primary data. Methods of data collection using a questionnaire. The data analysis method used is descriptive statistical test, validity test, reliability test, and classical assumption test (normality test, multicollinearity test, and heteroscedasticity test). Hypothesis testing using multiple linear regression test, F test, t test, and test the coefficient of determination. The results of this study are that the simultaneous application of government accounting standards, internal control systems, and human resource competencies affect the quality of financial reports. Partially the application of government accounting standards has a significant effect on the quality of financial reports, internal control systems and human resource competencies have no significant effect on the quality of reports. Keywords: Government Accounting Standards, Internal Control Systems, Human Resources Competence, Quality of Financial Reports